2011
DOI: 10.1007/s10562-011-0719-7
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study on the Adsorption of Formic Acid and Its Oxidized Intermediates on (100) Facets of Pt, Au, Monolayer and Decorated Pt@Au Surfaces

Abstract: In this work we have systematically characterized the adsorption of formic acid, its decomposed intermediates and products on the (100) surfaces of Pt, Au, monolayer and decorated Pt@Au surfaces. The calculated thermodynamic results validate our previous experimental results that the decorated Pt@Au surface may facilitate formic acid oxidation compared with the benchmark Pt catalyst; while the monolayer Pt@Au surface is not suitable for formic acid oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 77 publications
(100 reference statements)
4
30
0
Order By: Relevance
“…The latter orientation was found to adsorb with practically zero BE on all three surfaces. HCOOH* binds to the three facets via its carbonyl O atom on a top site with the OH and CH bonds pointing toward and away from the surface, respectively, and has a BE of −0.10 eV (−0.15 eV), −0.16 eV (−0.19 eV), and −0.21 eV on Au(111), Au(100), and Au(211), respectively. Formate has long been proposed as one of the key reaction intermediates in FA decomposition and has also been frequently cited as a possible intermediate in WGS and methanol synthesis reactions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The latter orientation was found to adsorb with practically zero BE on all three surfaces. HCOOH* binds to the three facets via its carbonyl O atom on a top site with the OH and CH bonds pointing toward and away from the surface, respectively, and has a BE of −0.10 eV (−0.15 eV), −0.16 eV (−0.19 eV), and −0.21 eV on Au(111), Au(100), and Au(211), respectively. Formate has long been proposed as one of the key reaction intermediates in FA decomposition and has also been frequently cited as a possible intermediate in WGS and methanol synthesis reactions.…”
Section: Resultsmentioning
confidence: 99%
“…This structural data is in agreement with the available experimental (NEXAFS and IR) and theoretical evidence. It has a BE of −1.69 eV (−1.82 eV), −2.02 eV (−2.10 eV), and −2.19 eV on Au(111), Au(100), and Au(211), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the Pt active sites of 600 C treated sample are not inhibited by intermediates (CO ads ). Yu and coworkers indicated that lattice contraction effect is beneficial for enhancing adsorption energies of HCOOH molecules onto the electrode surface, and promoting COOH with its H atom tilts downward towards the surface to make it very difficult to activate the CeH bond in HCOO to form the final product CO 2 afterwards [36]. Therefore, when the Pt 50 Au 50 /C catalyst was treated at 300e600 C, the catalytic activity was found to markedly increase with increasing treatment temperature, which could be attributed to lattice contraction effect.…”
Section: Electrocatalytic Activity For Formic Acid Oxidation Reactionmentioning
confidence: 99%